Directional Control of a Platoon of Vehicles for Comfort Specification by Considering Parasitic Time Delays and Lags - Ghasemi, Ali (Promet - Traffic&Transportation, 2013)
The problem of controlling a string of vehicles moving in one dimension is considered so that they all follow a lead vehicle with a constant spacing between successive vehicles. This paper is concerned by considering both effect of the parasitic time delays and lags and comfort specification. The Contribution of this paper is two-fold. Firstly, most physical systems often involve parasitic time delays and lags. Due to practical design and implementation, the negative effect of the parasitic time delays and lags on the string stability be taken into account Secondly, the aim here, however, is specifically to consider the restrictions which need to be imposed on the control parameters, in order to be well-suited with bounds on the dynamic variables as well as the requirement for string stability. At the end the robustness against the noise in the measurement signals factors are studied.